Impact of family and community medicine residency on performance indicators - Coelho, Guilherme; Kassada, Danielle Satie (O Mundo da Saúde, 2025)
This study aimed to evaluate the impact of implementing the Family and Community Medicine Residency Program on health indicators in Campinas, comparing the results with those of other Brazilian cities. The study employed an observational and descriptive design, analyzing secondary data obtained from the Primary Health Care Information System for the years 2018 to 2023. The analysis was conducted using Student’s t-test and the Difference-in-Differences (DiD) methodology. The results showed significant improvements in the mentioned indicators, with increases ranging from 3.61% to 85.09% in health indicators in Campinas, while the other cities did not show such substantial variations. These findings indicate a positive impact of the residency program on Primary Health Care, suggesting that the presence of family and community physicians contributed to improving the quality of and access to health services in Campinas. It is concluded that the continuation and expansion of the program are recommended, as well as the continuous monitoring of health indicators to ensure the sustainability of the achieved results.